Environmental, Social and Governance (ESG) and Corporate Financial Performance: Moderating Effects of Financial Slack - Inayati, Nur Isna; Rahmawati, Ika Yustina; Pandansari, Tiara; Hapsari, Ira; Ramadhani, Alfina Nur (Universitas Muhammadiyah Semarang, 2025)
This study explores the impact of ESG (environmental, social, governance) on company financial performance, particularly in manufacturing companies. In addition, this research also seeks to analyze whether high financial slack can strengthen the relationship between ESG, both collectively and separately, and the company's Return on Assets (ROA). The population focused on this study consists of 635 manufacturing companies operating in Indonesia, with a sample of 446 companies listed on the Indonesia Stock Exchange (IDX). The data used comes from annual and sustainability reports from 2018 to 2022. To analyze the data, this study employs linear regression analysis, including calculating coefficients, p-values, and R-squared. The study results show that the environmental, social, and governance variables do not have a significant relationship with the company's ROA, indicating that although ESG is considered important, its implementation in practice may not yet provide the expected impact on financial performance. Additionally, high financial slack was found not to strengthen the relationship between ESG and ROA, suggesting that more significant financial resources do not always guarantee improved sustainable performance. The implications of this study highlight the importance of companies effectively managing ESG aspects and financial resources to achieve sustainability. These findings also provide theoretical insights into the role of financial slack in the relationship between ESG and financial performance, emphasizing that companies need to be more proactive in integrating sustainability practices into their business strategies.